2000
DOI: 10.1093/hmg/9.13.2043
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a linkage disequilibrium between polymorphisms in the human estrogen receptor alpha gene and their relationship to bone mass variation in postmenopausal Italian women

Abstract: Bone mineral density (BMD), the major determinant of osteoporotic fracture risk, has a strong genetic component. The discovery that inactivation of estrogen receptor alpha (ERalpha) gene is associated with low BMD indicated ERalpha as a candidate gene for osteoporosis. We have investigated the role of three ERalpha gene polymorphisms [intron 1 PVU:II and XBA:I RFLPs and TA dinucleotide repeat polymorphism 5' upstream of exon 1] in 610 postmenopausal women. There was a strong linkage disequilibrium between intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
112
1
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(126 citation statements)
references
References 50 publications
12
112
1
1
Order By: Relevance
“…3). This polymorphism showed a bimodal distribution, with two peaks at 13 repeats (35.3% of alleles) and 21 repeats (10.9% of alleles), and a breakpoint at 18 TA repeats as reported previously [17][18][19]. This cutoff point was used to divide alleles into categories of either short (S<18 TA repeats) or long alleles (L≥18 TA repeats).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…3). This polymorphism showed a bimodal distribution, with two peaks at 13 repeats (35.3% of alleles) and 21 repeats (10.9% of alleles), and a breakpoint at 18 TA repeats as reported previously [17][18][19]. This cutoff point was used to divide alleles into categories of either short (S<18 TA repeats) or long alleles (L≥18 TA repeats).…”
Section: Resultsmentioning
confidence: 70%
“…It contains multiple promoter regions with alternative splice sites, resulting in expression of alternative first exons and different estrogen protein transcripts [22]. Thus (TA)n dinucleotide repeat lenght may affect alternative promoter and first exon usage resulting in different expression patterns [17]. Different expression patterns may affect the function of ESR protein and also the amounts of ESR1 protein that is produced.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The level of estrogen receptor in the cytosol of peripheral blood mononuclear cells is significantly lower in asymptomatic HBV carriers and patients with chronic hepatitis than in healthy controls, and administration of IFN-␣ increases its level in a dose-dependent manner in vitro and in vivo. 16,17 Together with the genetic effect of ESR1 polymorphism on several other clinical phenotypes, including breast cancer, 33 bone mineral density, 34 hypertension, 35 lipid levels, 36 coronary atherosclerosis, 37,38 and spontaneous abortion, 39 these illustrate the pleiotropic nature of the ESR1 protein. The estrogen/estrogen receptors axis can be simultaneously involved in several different metabolic pathways, including the reproductive system, bone, cardiovascular function, immune regulation, 40,41 liver function, 42,43 and HBV replication.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, increased bone mineral density, a potential surrogate marker of cumulative estrogen exposure and a predictor of breast cancer risk, 26 has also been associated with these SNP, 27,28 although not consistently. 29 These data suggest that the ESR1 2401 T/C and 2354 A/G polymorphisms may act as susceptibility or risk-modifying alleles for breast cancer. A study of 1,069 breast cancer cases and 1,166 controls in China recently reported a significant but modest increase in risk associated with the 2401 C allele (odds ratio [OR] 5 1.3 and 1.4 for heterozygotes and homozygotes, respectively).…”
mentioning
confidence: 83%